Membrane Sweeping for Vaginal Birth after Caesarean Section and its Outcome -A Comparative Study - Ramya, V. (J Clin Diagn Res, 2015)
INTRODUCTION: Sweeping of membrane is a method of induction of labour. This is used to avoid prolonged labour. However, there is paucity of data about the use of this method for induction of labour and reducing prolonged labour in pregnancy with previous caesarean section. This study is an effort to find the effect of membrane sweeping in previous caesarean section. OBJECTIVE: To initiate labour in previous LSCS patients by membrane sweeping and maternal outcome. STUDY SETTING: This prospective randomised control study was conducted in Mahatma Gandhi Medical College and Research Institute, Puducherry between January 2011 to June 2012. MATERIALS AND METHODS: Seventy five women were randomly assigned to membrane sweeping and seventy five to control. In study group serial membrane sweeping was done once weekly from 39 weeks of gestation until the onset of labour up to 41weeks of gestation. In control group, no intervention up to 41 weeks of gestation. All the cases were monitored by biophysical profile. OUTCOME MEASURES: The primary outcomes measured were number of patients who had onset of labour. The secondary outcome included the successful vaginal delivery, number of membrane sweeping to initiate labour, sweeping to delivery interval and amount of oxytocin required. RESULTS: The onset of labour in study group was 61.3% similar in control group 64% with p 0.736. The mean interval from sweeping to labour onset was 50.15±8 hours. The rate of VBAC was 17.3% in study group in compared to 18.7% in control group and LSCS was 82.7% in study group in compared to 81.3% in control group respectively. The mean gestation age at delivery 40±0.56 weeks for study group compared with 39.92±0.55 weeks for control group. CONCLUSION: Although membrane sweeping is an easy way of inducing labour, present study failed to demonstrate its beneficial effect on obstetrical outcome.